La maison de Saxe et la reconnaissance du roi Stanislas-Auguste par les cours du sud [1764-1766] - Bajer, Jakub (Studia Europaea Gnesnensia, 2012)
So far, the issue of recognition and legitimacy of king Stanislaus August on an international scene has not aroused any particular interest among Polish scholars. The aim of the author is to present the singular role which the children of the late king August III played in the matter of recognition of the new king elect by the courts of the so-called southern arrangement in 1764-1766. The period of the first two years of Stanislaus August’s reign was of paramount importance to the new king, since at the time he still enjoyed a relative freedom with regard to his Russian patroness, tsaritsa Catherine II. The new monarch devoted the time immediately following the election to the efforts to have his majesty recognized and then perhaps to form an alliance, even by marriage, with one of the Western states (France in particular), in order to consolidate his invariably weak position within the Republic itself, as well as his standing on the international scene with respect to Russia. Unfortunately, the countries opposing Russia and Prussia, belonging to arrangement which received the denomination of “southern” after the 7 Years War, namely France, Austria and Spain, recalled their representatives from Poland shortly before the election of Stanislaus August, thereby demonstrating their stand on the person of the new king, in whom they saw a Russian puppet. Moreover, thanks to the efforts of Marie Josephine of Saxony, daughter of the late king August III, sister of a new candidate to the throne and the Dauphine at the court of Versailles, it was decided that the recognition of the power of the new king should be withheld, until Saxon interests in Poland had not been properly secured, and until the Saxon supporters had not regained their former positions and properties. From the victorious election of Stanislaus August in September 1764, the losing French candidate, and at the same time a brother of Marie Josephine, crown prince Francis Xavier of Saxony, kept the family resolved not to accept envoys from the new king and not to enter any talks with him until the conditions set by the Saxon family had not been met. Thus, Saxony efficiently obstructed the recognition of Stanislas August by allied states, France, Austria and Spain, until October 1965 when the act of mutual renouncement of all financial claims on the part of Poland and Saxony had been signed and appropriate pensions and appanages voted by the Polish parliament for princes Francis Xavier and Charles of Kurland. Once the Saxon demands had been satisfied, Louis XV, Marie Therese and Charles III took the decision to recognise the majesty of Stanislaus August in early 1766.